Advantages of lignite addition in purification process of soil polluted by heavy metals - Król-Domańska, Katarzyna; Smolińska, Beata (Biotechnology and Food Science, 2012)
Environmental contamination by heavy metals represents a potential threat for plants, animal and humans. The metals do not undergo biodegradation. Many of them are soluble in water, therefore become more available for living systems and accumulate in the environment, especially in soil. This paper presents properties of brown coal(lignite) which show that this substance can be use as cheap and efficient sorbent in soil contaminated by heavy metals.